Pengaruh Model Problem Based Learning terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas XI Fase F SMA N 2 Padang - Marzufira; Amsari, Dina; Umar, Fahkrullah I Tama (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2023)
This study aims to determine the results of solving mathematical problems in class XI students of Phase F of SMA N 2 Padang using the PBL model of learning better than conventional learning. This research is a quasi-experimental design or quasi-experimental research. The population in this study were all of class XI phase F of SMA N 2 Padang. The results of students' mathematical problem solving increased in the experimental class as seen from the learning outcomes of students' problem solving ability tests with the t-test obtained t_count > t_table (2.472 > 1.995) data it shows H_0 is rejected and H_1 is accepted. From these calculations it can be concluded that there is an effect of learning mathematics problem based learning models on compound interest and annuity material on the results of the mathematical problem solving ability of class XI students phase F SMA N 2 Padang is better.